2023
DOI: 10.1111/exd.14785
|View full text |Cite
|
Sign up to set email alerts
|

The hub genes and their potential regulatory mechanisms in chronic spontaneous urticaria revealed by integrated transcriptional expression analysis

Abstract: Chronic spontaneous urticaria (CSU) is a recurrent disease characterized by wheals and or angioedema, and its pathogenesis is still unclear. The microarray datasets of skin tissue from CSU patients and healthy controls were integrated and analysed in Gene Expression Omnibus (GEO). Differentially expressed genes (DEGs) were identified using the NetworkAnalyst tool. Then, the Gene Ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed. Subsequently, a protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Most CSUs fall into the category of IgE-mediated type I hypersensitivity diseases. The cells involved in type I hypersensitivity reactions mainly include a variety of inflammatory cells such as mast cells, basophils, lymphocytes, eosinophils and neutrophils [ 24 , 25 ]. Among them, mast cells are mainly located in the skin and submucosal layer.…”
Section: Discussionmentioning
confidence: 99%
“…Most CSUs fall into the category of IgE-mediated type I hypersensitivity diseases. The cells involved in type I hypersensitivity reactions mainly include a variety of inflammatory cells such as mast cells, basophils, lymphocytes, eosinophils and neutrophils [ 24 , 25 ]. Among them, mast cells are mainly located in the skin and submucosal layer.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics is vital for analyzing genes in chronic urticaria. It manages and integrates diverse genetic and clinical data, detects variations associated with the condition, and elucidates disrupted pathways 17–19 . It studies gene expression, annotates functions, and constructs interaction networks to identify critical genes.…”
Section: Introductionmentioning
confidence: 99%
“…It manages and integrates diverse genetic and clinical data, detects variations associated with the condition, and elucidates disrupted pathways. 17 , 18 , 19 It studies gene expression, annotates functions, and constructs interaction networks to identify critical genes. Bioinformatics prioritizes relevant variants, compares genomes across populations, and employs machine learning for prediction.…”
Section: Introductionmentioning
confidence: 99%
“…As of now, two CSU studies have assessed skin gene expression ( 11 13 ), but joint analyses of these microarray datasets, GSE57178 and GSE72540 are limited. One recent study of these datasets recently reported that the IL-6/miR-149-5p/ZBTB20-AS1 axis may be involved in mast cell activation in CSU ( 14 ). The lesional immune cell infiltrate and core genes, however have not been investigated by bioinformatics analyses.…”
Section: Introductionmentioning
confidence: 99%